2011
DOI: 10.1287/mnsc.1100.1269
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Choice Under Cumulative Prospect Theory: An Analytical Treatment

Abstract: We formulate and carry out an analytical treatment of a single-period portfolio choice model featuring a reference point in wealth, S-shaped utility (value) functions with loss aversion, and probability weighting under Kahneman and Tversky's cumulative prospect theory (CPT). We introduce a new measure of loss aversion for large payoffs, called the large-loss aversion degree (LLAD), and show that it is a critical determinant of the well-posedness of the model. The sensitivity of the CPT value function with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(69 citation statements)
references
References 21 publications
0
64
0
1
Order By: Relevance
“…First, modeling the Disposition Effect with respect to Prospect Theory parameters appears to be too restrictive as investors in could also exhibit the opposite Disposition Effect (we refer to Weber et al (2014) for details of our dataset). In addition, 12 It should be noted that modeling portfolio strategies as in Vlcek and Hens (2011) is in line with theoretical models on static portfolio choice under Prospect Theory such as (Schmidt and Zank (2007), Jin and Zhou (2008), Bernard and Ghossoub (2010) and He and Zhou (2011)), who found that investors with Prospect Theory preferences may find corner solutions optimal and prefer full sales of existing positions (see Gomes (2005) for a CRRA-form of Prospect Theory and Polkovnichenko (2005) under rank-dependent Utility). Note that once multiperiod settings are considered, corner solutions are not necessarily optimal any longer (e.g.…”
Section: Prospect Theory: Fit For Finance? a Brief Reflection Of Relementioning
confidence: 69%
“…First, modeling the Disposition Effect with respect to Prospect Theory parameters appears to be too restrictive as investors in could also exhibit the opposite Disposition Effect (we refer to Weber et al (2014) for details of our dataset). In addition, 12 It should be noted that modeling portfolio strategies as in Vlcek and Hens (2011) is in line with theoretical models on static portfolio choice under Prospect Theory such as (Schmidt and Zank (2007), Jin and Zhou (2008), Bernard and Ghossoub (2010) and He and Zhou (2011)), who found that investors with Prospect Theory preferences may find corner solutions optimal and prefer full sales of existing positions (see Gomes (2005) for a CRRA-form of Prospect Theory and Polkovnichenko (2005) under rank-dependent Utility). Note that once multiperiod settings are considered, corner solutions are not necessarily optimal any longer (e.g.…”
Section: Prospect Theory: Fit For Finance? a Brief Reflection Of Relementioning
confidence: 69%
“…22 However, contrary to the case when Ω > 0 the household does not reduce the consumption gap but widens this gap. This means that the household increases its consumption even more than the Joneses do.…”
Section: (Iv) Limmentioning
confidence: 92%
“…Use of benchmark tracking in portfolio selection and management can be found in [Gaivoronski, Krylov & van der Wijst, 2005] and [Lioui & Poncet, 2013]. Similarly, use of reference points in portfolio selection and dependence of the optimal risky exposure on the reference point is in [He & Zhou, 2011]. Penalty costs and benchmark targets in pension funds optimization appear in [Geyer & Ziemba, 2008].…”
Section: The Modelmentioning
confidence: 99%